2012
DOI: 10.1056/nejmoa1202753
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and Biomarker Changes in Dominantly Inherited Alzheimer's Disease

Abstract: BACKGROUND The order and magnitude of pathologic processes in Alzheimer’s disease are not well understood, partly because the disease develops over many years. Autosomal dominant Alzheimer’s disease has a predictable age at onset and provides an opportunity to determine the sequence and magnitude of pathologic changes that culminate in symptomatic disease. METHODS In this prospective, longitudinal study, we analyzed data from 128 participants who underwent baseline clinical and cognitive assessments, brain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

138
2,757
7
30

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 3,238 publications
(3,039 citation statements)
references
References 29 publications
138
2,757
7
30
Order By: Relevance
“…The levels of tau in CSF are being used as a complementary biomarker, and the quantification of both t‐tau and p‐tau (threonine 181) have been validated by frequent testing of human CSF samples in several clinical studies. Increased concentration of tau was detected almost 15 years before the onset of symptoms was expected in the CSF of AD patients 38. A growing number of studies point to the roles of oligomeric assemblies of pathogenic proteins in toxicity and propagation of AD.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of tau in CSF are being used as a complementary biomarker, and the quantification of both t‐tau and p‐tau (threonine 181) have been validated by frequent testing of human CSF samples in several clinical studies. Increased concentration of tau was detected almost 15 years before the onset of symptoms was expected in the CSF of AD patients 38. A growing number of studies point to the roles of oligomeric assemblies of pathogenic proteins in toxicity and propagation of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Trajectory‐based models that are informed by patient data have been proposed that employ linear mixed models44 or quantile regression,45 with the latter allowing for nonmonotonic trajectories. However, these models require an a priori definition of disease stage; in the cited examples, this is expected age to onset and time to diagnosis, respectively, both of which need to be estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Prior major cohort studies have reported that plasma A β is a risk factor or predictive marker for AD onset in healthy older community members aged at least 55 years 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12. In contrast, after analyzing fasting blood samples from healthy individuals of a wide age range, we observed the natural course of and factors affecting plasma A β 40 and A β 42.…”
Section: Discussionmentioning
confidence: 99%
“…The Alzheimer's Disease Neuroimaging Initiative (ADNI) and the Dominantly Inherited Alzheimer Network (DIAN) have confirmed the efficacy of neuropsychiatric tests and neuroimaging using cerebrospinal fluid (CSF) biomarkers, including amyloid PET, demonstrating that signatures of brain A β amyloidosis can be found approximately 30 years before the onset of dementia 10, 11. Recent studies have clarified that the plasma A β 42/40 ratio is inversely correlated with cortical amyloid burden in AD, which can be converted into MCI,12, 13 and that the plasma A β 42/40 ratio is a useful screening marker for brain A β amyloidosis in normal individuals 14, 15.…”
Section: Introductionmentioning
confidence: 99%